2009
DOI: 10.1631/jzus.b0820220
|View full text |Cite
|
Sign up to set email alerts
|

Response enhancement of olfactory sensory neurons-based biosensors for odorant detection

Abstract: This paper presents a novel strategy for the response enhancement of olfactory sensory neurons (OSNs)-based biosensors by monitoring the enhancive responses of OSNs to odorants. An OSNs-based biosensor was developed on the basis of the light addressable potentiometric sensor (LAPS), in which rat OSNs were cultured on the surface of LAPS chip and served as sensing elements. LY294002, the specific inhibitor of phosphatidylinositol 3-kinase (PI3K), was used to enhance the responses of OSNs to odorants. The respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…to investigate the possibilities. Our data showed that one of the PI-3 kinase inhibitors, LY294002 (Wu et al, 2009), blocked the effect of TGF-β1 in LLC-PK1 cells. It is unlikely that this was a systemic inhibitory effect of LY294002, or a non-specific effect, because it took effect even at 10 µmol/L, a very low concentration that generally has no systemic effect on mRNA expression.…”
Section: Discussionmentioning
confidence: 53%
“…to investigate the possibilities. Our data showed that one of the PI-3 kinase inhibitors, LY294002 (Wu et al, 2009), blocked the effect of TGF-β1 in LLC-PK1 cells. It is unlikely that this was a systemic inhibitory effect of LY294002, or a non-specific effect, because it took effect even at 10 µmol/L, a very low concentration that generally has no systemic effect on mRNA expression.…”
Section: Discussionmentioning
confidence: 53%
“…They also include some synthetic substances similar to biological substances, such as aptamers, peptides, and molecularly imprinted polymers. The biological materials used in odor biosensors are mainly extracted from the creatures' olfactory systems, for example, olfactory epithelium [32], olfactory sensory neuron (OSN) [33], olfactory receptor (OR) protein [34][35][36], and odorant binding protein (OBP) [37,38]. These odor biosensors have higher sensitivity and selectivity towards their ligands than conventional odor sensors, and also they are not sensitive to temperature and humidity changes.…”
Section: Introductionmentioning
confidence: 99%
“…Biosensors 2023, 13, x FOR PEER REVIEW 2 of 23 creatures' olfactory systems, for example, olfactory epithelium [32], olfactory sensory neuron (OSN) [33], olfactory receptor (OR) protein [34][35][36], and odorant binding protein (OBP) [37,38]. These odor biosensors have higher sensitivity and selectivity towards their ligands than conventional odor sensors, and also they are not sensitive to temperature and humidity changes.…”
Section: Introductionmentioning
confidence: 99%
“…They are useful in understanding the signal processing mechanism of olfactory systems. Therefore many mathematical models of olfactory systems have been applied to pattern recognition, often with remarkable results, which help to understand the olfactory information processing (Liljenström and Wu, 1995;Kozma et al, 2003;Gonzalez et al, 2007;Li G. et al, 2007;Li X. et al, 2006;Ma and Krings, 2009;Wu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%